Knowledge, Skills and Values: Balancing Legal Education at a Transforming Law Faculty in South Africa - Dednam, Martin (South African Journal of Higher Education, 2016)
Determining curriculum content for legal education is difficult having to consider the value of universal foundational teaching-learning as opposed to dedicated practical legal education; emphasizing generic skills development as opposed to accumulation of knowledge or practical skills. Finding an equilibrium between these competing forces and having to consider ‘non-educational’ forces, including expectations of transformation and redress, make the task more complex. This article illuminates challenges regarding the balanced development of knowledge, skills, values, and transformation, and introduces specific initiatives to help students develop especially their ability to write well. It contends that any adversary stances of the academe versus the professions will only be solved by clarity and agreement on the meanings, scope and contextual application of concepts like general and subject knowledge, generic skills and practical skills, and scholarly and professional values. Skills training as a generally accepted outcome should be dissected to clearly indicate the generic or specific purpose thereof, implying a narrower definition of outcomes but also preparation of lecturers to be competent to attain these outcomes with educational expertise.